Are miserly budgets putting businesses at risk of cyber-attack?. Issue 8 (August 2018) - Brown, Tim
Abstract : If you perform a search of the term 'ransomware' on Google, you will see two things. The first is a definition of WannaCry, the ransomware attack that, on 12 May 2017, spread around the world and affected hundreds of targets, including public utilities, large corporations and, most notably, crippled the NHS in the UK. 1 But you'll also see a series of news stories and, regardless of what day you type 'ransomware' into the search bar, you're likely to see stories of attacks from just days ago, or, in some cases, just hours ago. All businesses are at risk of cyber-attacks that are all too often successful. Is this due to a lack of budget, or are budgets being spent in the wrong way? Would simply spending more money be enough to help? All businesses face budget pressures – which means they need to understand how to spend their budgets wisely. And this is where managed service providers (MSPs) can play a crucial role. Tim Brown of SolarWinds explains how MSPs can supply the skills and expertise to ensure that businesses have the right combination of technology and personnel.